Cerebrospinal fluid immunoglobulins in cysticercosis of the central nervous system - A. Spina-França; J. A. Livramento; L. A. Bacheschi; P. Garcia-Lopes (Arquivos de Neuro-Psiquiatria)
Investigation on the behavior of immunoglobulins IGG, IGA and IGM in the CSF in cases of cysticercosis of the CNS, based on data pertaining to two different series of cases. The first series comprises 30 samples of CSF, and the second one, 5 samples. It was demonstrated that IGG is the one representing the largest contingent. IGG concentration keeps in proportion with the gamma globulin concentration, of which it represented an 88% average in the cases studied. Participation of IGG in the protein profile of the CSF is greater than the usually referred; the results for the material analyzed showed 16%. It was verified a proporcionality also between IGG concentration and the titer of positive complement fixation test for cysticercosis; there is a positive correlation, whose numerical expression was found to be significant, in the samples studied.